2003
DOI: 10.1002/mop.10935
|View full text |Cite
|
Sign up to set email alerts
|

T‐coupled circular microstrip antenna with H‐shaped aperture for bandwidth and radiation‐gain improvements

Abstract: A novel design of a T-coupled

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Although the angle of the arch that is formed by the two branches can be the third parameter for impedance matching in the case of circular meshed patches, it was found that the optimal coupling performance can be achieved when it is 60 • [15]. Other benefits of this feeding technique include low insertion loss in dual-port application [17] and improved gain and bandwidth [18]. While it is true that such a feed line may decrease the overall transparency of the antenna, the thick microstrip line can be placed on top of the cover glass above one of the gaps (G in Fig.…”
Section: Meshed Patch Antenna Topologymentioning
confidence: 99%
“…Although the angle of the arch that is formed by the two branches can be the third parameter for impedance matching in the case of circular meshed patches, it was found that the optimal coupling performance can be achieved when it is 60 • [15]. Other benefits of this feeding technique include low insertion loss in dual-port application [17] and improved gain and bandwidth [18]. While it is true that such a feed line may decrease the overall transparency of the antenna, the thick microstrip line can be placed on top of the cover glass above one of the gaps (G in Fig.…”
Section: Meshed Patch Antenna Topologymentioning
confidence: 99%
“…The initial values for the coupling distance, length and the width of the brunch lines (Fig. 3-a) were taken referencing Zhu [3] and Liu [4], and then were refined during the simulation.…”
Section: Circular Meshed Patch Antennamentioning
confidence: 99%